Huffmanela lusitana sp. n. (Nematoda: Trichosomoididae) infecting pouting, Trisopterus luscus (Teleostei: Gadidae) off the Atlantic coast of Portugal. (August 2019) - Ramos, Paula; Carvalho, Raquel; Rosa, Fernanda; Alexandre-Pires, Graça; Seixas, Fernanda; Esteves, Alexandra; Huffman, David
Abstract: Some pouting caught off the Atlantic coast of Portugal are discarded as unmarketable due to a dark discolouration of the skin and muscle. This study investigates the cause of this condition, describes the new parasite species responsible, and highlights the importance of educating those in charge of premarket inspection of food fish in order to reduce likelihood that consumers will eat infected fish. Macroscopically, infected fish showed considerable heterogeneity in darkening of the skin and hypaxial and epaxial muscles. Microscopical observation revealed bipolar nematode eggs in varying stages of development arranged in a linear pattern along muscle fibers. Histopathology confirmed the presence of eggs of a nematode of the genus Huffmanela Moravec, 1987 as the cause of muscle darkening and established a relationship between infection intensity and consequent darkened appearance of the tissues. The eggs are oval or barrel-shaped, with a smooth surface and polar plugs at opposite ends. The thin outer vitelline membrane is smooth and lacks ornamentation. Under light microscopy, the main eggshell of older eggs exhibits the outermost delicate and smooth vitelline membrane, and a thicker layer, correspondent to chitinous and chondroitin proteoglycan layers. Scanning electron microscopy of eggs confirmed light microscopic studies, namely the presence of a smooth vitelline membrane surrounding the egg. Microscopic and ultrastructural characteristics of eggs, and a new host family in a new geographic area, all suggest that a new species, herein named Huffmanela lusitana sp. n. is involved. Graphical abstract: Image 1 Highlights: Huffmanela lusitana sp. n in Trisopterus luscus . Dark muscle due to Huffmanela eggs. H. lusitana sp. n as the cause of disgusting aspect of infected fish meat. H. lusitana sp. n as a zoonotical potential infection to consumers. H. lusitana sp. n. as a constraint factor of healthy wildlife stocks.